Relationship between video game addiction and bladder/bowel dysfunction in children. - Tiryaki, Öznur; Menekşe, Dilek; Çınar, Nursan (Biomédica: Revista del Instituto Nacional de Salud, 2024)
Introduction. Video games have a strong influence on children and adolescents. Video game addiction has negative effects on children's health. Objective. To determine the relationship between video game addiction and bladder/bowel dysfunction in children. Materials and methods. Three hundred sixty-three children and their mothers who met the inclusion criteria constituted the sample of this correlational study. The data were collected using a descriptive information form, the Video Game Addiction Scale for Children, and the Childhood Bladder and Bowel Dysfunction Questionnaire. Results. We found that 72.5% of the children were nine years old and 27.5% were ten years old; 50.4% were males and 49.6% were female. While 4.7% of the children who participated in the study were underweight, 19.6% were overweight, and 17.9% were obese. The mean Video Game Addiction Scale for Children score was 50.77 ± 16.17, whereas the mean Childhood Bladder and Bowel Dysfunction Questionnaire score was 29.98 ± 8.90. The ratio of children with a mean Video Game Addiction Scale for Children scores equal to or greater than 90 was 0.8% (n = 3). We found that 3.6% (n = 13) of the children had urinary/fecal incontinence while playing video games. There was a weak positive relationship between the dimensions of the Video Game Addiction Scale for Children scores, the Childhood Bladder and Bowel Dysfunction Questionnaire scores, and children's bladder and bowel function (r = 0.220; p ˂ 0.05). Conclusions. There is a correlation between children's video game addiction level and their bladder and bowel dysfunction grade. Higher video game addiction levels correspond to higher bladder and bowel dysfunction.